Inhibitory effects of plant phenolic compounds on enzymatic and cytotoxic activities by a snake venom phospholipase A2 (2023)
Polyphenolic compounds have shown to inhibit toxic effects induced by snake venom proteins. In this work, we demonstrate that gallic acid, ferulic acid, caffeic acid, propylgallate and epigallocatechingallate inhibit the enzymatic activity of a phosphol.